HUBUNGAN TINGKAT KEPUASAN PENGGUNAAN FASILITAS RUANGAN KELAS DENGAN TINGKAT KENYAMANAN MAHASISWA PADA SAAT PROSES PEMBELAJARAN DI STIKES WIRA HUSADA YOGYAKARTA. - Fransiskus Asisi Gandur; Akhmad Toha; Priana Tri Widyastiti (MIKKI (Majalah Ilmu Keperawatan dan Kesehatan Indonesia), 2014)
ABSTRACTBackground: The cause of Indonesian educational quality poorness was teaching effectiveness, efficiency, and standardization. From observational result conducted in School of Health Science Wira Husada Yogyakarta, it was obtained that there were students who attend classes they sometimes did not get class room due to class room availability.  Objective: To know relation the degree of satisfaction use in the class room amenity with the degree of  comfortable student at learn process in School of Health Science Wira Husada Yogyakarta. Method: This was a quantitative non-experimental research with a cross sectional approach. Data collection used questionnaire. Data analysis used spearman rank (rho) correlation test. Result: Spearman Rank correlation test (rho) was obtained result of 0.789. Satisfied category result was (64.6%), not satisfied was (19%), very satisfied was (16.4%). Convenient category was (68.4%), inconvenient was (15.2%), very convenient was (13.9%) and very inconvenient was (2.5%).Conclusion: There was a strong relation between the degree of satisfaction use in the class room amenity with the degree of comfortable student at learn process in School of Health Science Wira Husada Yogyakarta.